2003
DOI: 10.1002/ptr.1137
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal compounds from Zanthoxylum chiloperone var. angustifolium

Abstract: An alkaloidal extract of the stem barks of Zanthoxylum chiloperone var. angustifolium exhibited antifungal activity against Candida albicans, Aspergillus fumigatus and Trichophyton mentagrophytes var. interdigitale using a TLC bioautographic method. Bioassay-guided fractionation of this extract resulted in the isolation of two active compounds identi fi ed as canthin-6-one and 5-methoxycanthin-6-one. Canthin-6-one exhibited a broad spectrum of activities against Aspergillus fumigatus, A. niger, A. terreus, Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 9 publications
0
39
0
2
Order By: Relevance
“…A decoction of Z. chiloperone root and stem bark has been used in traditional medicine to treat malaria and for its emmenagogue and antirheumatic properties (Ferreira et al, 2007;Milliken, 1997). Recent studies have shown that the crude extract of the stem bark and leaves have activity against Trypanosoma cruzi (Ferreira et al, 2011;Ferreira et al, 2002) and antifungal activity in vitro (Thouvenel et al, 2003). Further investigations demonstrate that canthinone type alkaloids, canthin-6-one and 5-methoxycanthin-6-one, are antifungal (Soriano-Agatόn et al, 2005;Thouvenel et al, 2003) and effective in vivo against Leishmania amazonensis and Trypanosoma cruzi (Ferreira et al, 2011;Ferreira et al, 2007;Ferreira et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decoction of Z. chiloperone root and stem bark has been used in traditional medicine to treat malaria and for its emmenagogue and antirheumatic properties (Ferreira et al, 2007;Milliken, 1997). Recent studies have shown that the crude extract of the stem bark and leaves have activity against Trypanosoma cruzi (Ferreira et al, 2011;Ferreira et al, 2002) and antifungal activity in vitro (Thouvenel et al, 2003). Further investigations demonstrate that canthinone type alkaloids, canthin-6-one and 5-methoxycanthin-6-one, are antifungal (Soriano-Agatόn et al, 2005;Thouvenel et al, 2003) and effective in vivo against Leishmania amazonensis and Trypanosoma cruzi (Ferreira et al, 2011;Ferreira et al, 2007;Ferreira et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the crude extract of the stem bark and leaves have activity against Trypanosoma cruzi (Ferreira et al, 2011;Ferreira et al, 2002) and antifungal activity in vitro (Thouvenel et al, 2003). Further investigations demonstrate that canthinone type alkaloids, canthin-6-one and 5-methoxycanthin-6-one, are antifungal (Soriano-Agatόn et al, 2005;Thouvenel et al, 2003) and effective in vivo against Leishmania amazonensis and Trypanosoma cruzi (Ferreira et al, 2011;Ferreira et al, 2007;Ferreira et al, 2002). Canthin-6-one has been suggested to be an inexpensive and safe treatment for use in long-term oral treatment as well as a good candidate against drug resistant strains of T. cruzi.…”
Section: Introductionmentioning
confidence: 99%
“…One of the colorless compounds, C 14 H 8 N 2 O, was identified by its spectroscopic data, including the 1 H-coupled 13 C NMR spectrum, [1] as canthin-6-one (1), [2] an alkaloid known from several plants of the Rutaceae, Simaroubaceae, and Amaranthaceae families. [3] Canthin-6-one exhibits antifungal [4] and cytotoxic [5] properties. A second colorless compound 2, C 15 H 10 N 2 OS, is a methylthio derivative of canthin-6-one.…”
Section: Resultsmentioning
confidence: 99%
“…Tribos indígenas do Paraguai usa a espécie como antimalárico, enemagogo, anti-reumático, antimicrobiano e para dor de cabeça (Milliken 1997;Guy et al, 2001). Estudos fi toquímicos de Z. chiloperone identifi caram alcalóides e óleos essenciais (SorianoAgatón et al, 2005;Thouvenel et al, 2003;Ferreira et al, 2002). Atividades leishmanicida e antifúngica (Thouvel et al, 2003;Ferreira et al, 2002), assim como tripanomicida (Ferreira et al, 2007), foram atribuídas a substâncias isoladas desta espécie.…”
Section: Introductionunclassified